PENANGANAN KELUHAN MELALUI SISTEM INFORMASI DAN KOMUNIKASI HELPDESK PT. KINARYA TUNAS ARTHA - Bagus Priyatna, Dion; Alief Nurrohman, Muhammad; Evi Yuliana, Margaretha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
In the ever-growing digital era, information & communication technology has become a key aspect in running various types of businesses, organizations and institutions. The demand for information and the use of computer applications has encouraged the development of applications that can overcome activities and problems during operational processes at the PT Kinarya Tunas Artha company. However, there are obstacles in handling complaints regarding IT equipment at three separate factory locations, and reporting data processing is carried out manually via WhatsApp instant messages. Therefore, this research aims to implement a web-based helpdesk information system that makes it easier for users to report complaints to IT staff, speeds up IT staff responses, and provides an in-depth understanding of the concepts and best practices in helpdesk information & communication systems. Helpdesk information systems help companies respond quickly to problems, optimize resource allocation, and provide data for analysis and continuous improvement, improving the efficiency and quality of customer service and resource management.